Ulcerative colitis in an adult patient mimicking Henoch–Schönlein purpura: A case report. Issue 35 (August 2018) - Lu, Bin; Niu, Li-Li; Xu, Xi-Guang; Yao, Shu-Lan; Tan, Xing-You
Abstract: Rationale: Ulcerative colitis (UC) is one of the chronic inflammatory diseases of the intestinal tract. UC being misdiagnosed as Henoch–Schönlein purpura (HSP) in the elderly has seldom been reported about. Patient concerns: A 64-year-old man was admitted to the hospital with petechiae and palpable purpura in lower limbs and abdominal pain for about 1 month. Diagnoses: Colonoscopy demonstrated severe inflammation in the colon, mucosal congestion, and edema, and multiple hemorrhages and ulcerations, with purulent adhesions. A histopathologic examination of the colon biopsies revealed extensive infiltration of immune cells and mucosal ulcerations in the intestine. UC was diagnosed. Interventions: The patient was treated with prednisone (1.0 mg/kg/d) with progressive dose reduction. Outcomes: The skin lesions were healed within 4 weeks, and his abdominal pain was alleviated remarkably. He is currently under follow-up. Lessons: As the treatment used for patients with HSP was not effective, it was advised that UC should be taken into consideration.